TECHNOPRENEUR TRAINING MODEL IN BUILDING AN ENTREPRENEURSHIP - Permana, Asep Yudi; Srihartati, Raden Diah; Akbardin, Juang; Setiawan, Agung; Jatnika, Dudung; Rustandi, Wandi (Universitas Pendidikan Indonesia, 2020)
Abstract - The use of cutting-edge technology is appropriate for business development based on an established entrepreneurial spirit that will optimize the process as well as the results of the developed business unit. This is what is called technopreneurship: a collaboration between the application of technology as an instrument and an independent business spirit as a necessity. In an era of intense global competition, business innovation must be accompanied by various kinds of technological engineering in order to multiply the performance of the business. Technopreneurship is an integral character between competency in applying technology and the spirit of building a business. From here, a technological business unit grows: a business unit that utilizes applied technology in the process of innovation, production, marketization, etc. Communication and information technology or telematics technology (information and communication technology (ICT) has been recognized by the world as one of the means and the main infrastructure to tackle the world's problems.The Community Service Program with the title Technopreneur Training in Building an Entrepreneurial Spirit for Prospective Architects in the Field of Consulting Services and Construction Services at the University of Education of Indonesia is implemented to provide entrepreneurial skills for students to have entrepreneurial mentality and skills (entrepreneurship) and form a Campus business incubator unit. This program selects and guides 21 students to become independent micro entrepreneurs. The method used in this program is practical learning based on business projects by training and assessing the ability of students to start and run a business based on 4 assessment criteria which include: personality, cooperation, leadership and online marketing skills to increase competitiveness and overcome constraints of limited production funding. The implementation of this KDP includes 4 stages consisting of recruitment, approach, implementation, and monitoring evaluation of 20 prospective tenants for 8 months. From these activities, it is expected that 10 tenants will become independent entrepreneurs and 5 people are still not successful.